Association of Risk Factors and Glycemic Status in Hospital Patients of Different Types of Myocardial Infarction in a Tertiary Care Hospital (Bangladesh Critical Care Journal, 2017)
Background: Glycometabolic state at hospital admission is an important risk marker for long-term mortality in patients with acute myocardial infarction. Our aim was to ascertain the associated risk factors and glycemic status in patients with different types of myocardial infarction, and to assess whether such abnormalities can be identified in the early course of myocardial infarction.Methodology: This cross sectional observational study was carried out enrolling 100 subjects with ST elevation (42 subjects) and non ST elevation (58 subjects) myocardial infarction, in the Department of Cardiology, BIRDEM General Hospital, Shahbagh, Dhaka, over a period of six months from January 2012 to June 2012. We did fasting blood glucose and glycatedhaemoglobinA1C (HbA1C) level next day following admission with or without history ofdiabetes mellitus and observed the difference between two types of myocardial infarction (ST elevation and non ST elevation ).Results: Mean age and gender difference was significant between ST elevation and non ST elevationmyocardial infarction. Significant differences in pre-existing risk factors such as Diabetes (95.2%,vs 86.2% ), Dyslipidemia (72.91%, vs 44.82%), Hypertension (79.16%, vs 36.2%) and family history of Ischemic Heart Disease(75%, vs 29.31%) were observed between ST elevation and non ST elevation groups. It was revealed that mean fasting blood glucose (FBG) in ST elevation and non ST elevation was 10.23 mmol/l and 8.42 mmol/l respectively. Mean HbA1C level was 9.2% and 8.9% in ST elevation and non ST elevation. Significant difference in fasting blood glucose and HbA1C was observed between ST elevation and non ST elevation group.Conclusion: Glycemic status is relatively more uncontrolled in ST elevated MI and must be managed with all possible therapeutic modules to minimize further complications.Bangladesh Crit Care J March 2017; 5(1): 3-6